Evaluation of maxillary sinus pathologies and the posterior superior alveolar artery canal using cone-beam computed tomography - Melike Gulec; Veysel Icen; Elif Esra Ozmen (BMC Oral Health)
Abstract Objective This study aims to determine the anatomical relationship between the posterior superior alveolar artery (PSAA) and the lateral wall of the maxillary sinus during preoperative radiological evaluations in the posterior maxillary dental region, as well as to evaluate the prevalence of PSAA and its potential associations with sinus pathologies. Materials and methods This retrospective study is based on the analysis of Cone-Beam Computed Tomography (CBCT) data from 510 sinuses of 255 patients. The visibility of the PSAA vascular canal, artery diameters, vertical distance between the alveolar crest and the artery, and the distance to the sinus floor were measured in coronal sections. Additionally, the relationships between sinus pathologies and septa within the sinuses and the PSAA were evaluated. Results PSAA was detected bilaterally in the majority of patients (70.2%). Sinus pathologies and the presence of septa were also examined, revealing that 36.9% of the sinus pathologies were bilateral. Chi-square analyses showed no statistically significant relationship between gender and the presence of PSAA. Female patients had a higher incidence of sinus pathologies compared to males (p = 0.002). No significant relationship was found between the presence of PSAA and septa. Conclusions This study highlights the importance of considering the anatomical position and prevalence of the PSAA during preoperative radiological evaluations in the posterior maxillary region. This study identified the PSAA as predominantly located in the lateral wall of the maxillary sinus, an anatomical feature of critical importance during preoperative radiological evaluations to minimize vascular complications. Clinical trial number Not applicable.